1979
DOI: 10.1073/pnas.76.6.3034
|View full text |Cite
|
Sign up to set email alerts
|

Receptoral and postreceptoral visual processes in recovery from chromatic adaptation.

Abstract: The time course of recovery from chromatic adaptation in human vision was tracked by determining the wavelength of light that appears uniquely yellow (neither red nor green) both before and after exposure to yellowish green and yellowish red adapting lights. Recovery is complete within 5 min after steady light exposure. After exposure to the alternating repeated sequence 10-sec light/b-sec dark, the initial magnitude of the aftereffect is reduced but recovery is retarded. The results are interpreted in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Benzchawel & Guth, in press;Eisner & MacLeod, 1981;Finkelstein & Hood, 1981;Jameson, Hurvich, & Varner, 1979;Pugh & Mollon, 1979;Stabell & Stabell, 1975;Stromeyer & Sternheim, 1981;Valeton & van Norren, 1979;Wandell & Pugh, 1980). Stabell and Stabell found scotopic color contrast effects after short-term (lO-sec) chromatic adaptation, although they did not explicitly discuss the locus of the effects, and Jameson et al found changes in unique yellow lasting several minutes which they ascribed to postreceptoral opponent color processes after intermittently (10 sec on, 10 sec off) adapting the eye to colored stimuli for 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…Benzchawel & Guth, in press;Eisner & MacLeod, 1981;Finkelstein & Hood, 1981;Jameson, Hurvich, & Varner, 1979;Pugh & Mollon, 1979;Stabell & Stabell, 1975;Stromeyer & Sternheim, 1981;Valeton & van Norren, 1979;Wandell & Pugh, 1980). Stabell and Stabell found scotopic color contrast effects after short-term (lO-sec) chromatic adaptation, although they did not explicitly discuss the locus of the effects, and Jameson et al found changes in unique yellow lasting several minutes which they ascribed to postreceptoral opponent color processes after intermittently (10 sec on, 10 sec off) adapting the eye to colored stimuli for 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…The attenuation of human flicker sensitivity, consequent to adaptation, is evident in both behavioral (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and neural (9,23,24) response measures, but its frequency dependence has never been assessed systematically. Here we measure the reduction in flicker sensitivity after prolonged exposure, or adaptation, to both luminance and chromatic flicker across a wide range of frequencies.…”
mentioning
confidence: 99%
“…Here we pursue these questions through an experimental design that exploits, as a functional landmark, the known process of flicker adaptation, by which flicker sensitivity of an observer is attenuated after prolonged exposure to flickering lights (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The attenuation of human flicker sensitivity, consequent to adaptation, is evident in both behavioral (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and neural (9,23,24) response measures, but its frequency dependence has never been assessed systematically.…”
mentioning
confidence: 99%
“…The results of Jameson et al (1979), Hansel and Mahmud (1978), and Mahmud (1987) all suggest that the aftereffects observed on the homogeneous fields are not contingent aftereffects. This suggestion is certainly consistent with our findings in Experiment 3.…”
Section: Discussionmentioning
confidence: 67%
“…One possible account for this effect is that there is some overall shift in color balance that is not very closely tied to, or dependent on, a match between retinal contours in induction and test; in short, it is not a contingent aftereffect. Research by Jameson, Hurvich, and Varner (1979) suggests such a possibility. They found that viewing a colored light source alternating with a blank field produced a shift in perceived color that persisted for at least 15 min (no measurements were made beyond 15 min).…”
Section: Discussionmentioning
confidence: 95%